Pengaruh PET Sebagai Bahan Tambah Aspal Terhadap Nilai Kekuatan Sisa Campuran Asphalt Concrete-Binder Course (AC-BC) - Wibisono, Andryan; Putra, Sasana; Junaedi, Tas'an; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Road damage often occurs due to excessive volume of heavy vehicles so that vehicle loads cause strain and stress of the pavement layer. One way to improve the quality of asphalt mixtures is by adding PET plastic. Research was conducted to determine the effect of AC-BC mixtures with the addition of PET plastic waste as a binder additive in asphalt on Marshall parameters and Durability of Residual Strength Index. Based on the results of the study, the specific gravity of asphalt increased as the level of PET mixed increased. The penetration value decreases as the PET content increases because the asphalt becomes harder. Ductility decreases as more PET content makes the asphalt more brittle. The softening point value increases as the PET content increases because the wax content in the asphalt increases. In the durability test, the largest IKS value occurred in the mixture of asphalt penetration 60/70 + 4% PET at 94.58%; asphalt penetration 60/70 + 2% PET made an IKS value of 94.00%; asphalt penetration 60/70 + 3% PET made an IKS value of 94.36%; and asphalt penetration 60/70 + 0% PET had the smallest IKS value of 91.58%. All IKS values have met the minimum Bina Marga standard of 90%. Therefore, the greater the percentage of PET mixed, the greater the IKS value.